Application of Accrual Basis in the Public Sector and its Role in Providing Useful Information Exploratory Study of a Sample of Academic Specialists in the Kurdistan Region of Iraq - Dler Mousa Ahmed; Farhad Al-kake (QALAAI ZANIST JOURNAL, 2019)
The goal of this research is to clarify the role of the shift from the applying of cash basis to the accrual basis in the public sector in Kurdistan Region of Iraq. Cash basis provide more useful information to users that help them to make right decisions. To achieve the objectives of the study was developed questionnaire included (12 questions) distributed on 120 academic professionals in the Kurdistan Region Iraq, and collected 96 of them. The researchers reached a number of conclusions after analyzing questionnaire's questions. The most important of these conclusions is that the application of the cash basis in the public sector provides information that has appropriate, credible, more understanding, comparable, and more realistic and meet the decision models. The two researchers also made a number of recommendations, including the need to transform from cash basis to the accrual basis by the Kurdistan Regional Government of Iraq. This shifting can be gradual, passes through stages such as firstly applying modified cash basis adjusted, secondly applying modified accrual basis and finally apply full accrual basis.